English Vlog Project: Students’ Perceptions and Their Problems - Fitria, Tira Nur (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
Vlogging can help language learners to practice even improve their speaking skills. This research is to know the non-English students’ perception and their problems of making an “English Vlog” project at ITB AAS Indonesia in 2020/2021. This research applies descriptive qualitative. The analysis shows that most students strongly agree that speaking is the most challenging skill. But, they agree that the English vlog is an interesting and fun task in English class in making them dare to speak in English. The topic/theme about "My Description" also is interesting. Before, most students prepare a draft before recording an English vlog and prepare by writing an Indonesian draft first. They do the exercises repeatedly to get the best result with more than five times in making an English vlog. But, the students also face problems in making English vlogs, they are Mostly students having difficulty in grammar when speaking English. Most students use a phone in recording their vlog and they do not use additional devices when recording English vlog. The audio and video quality on their device affects their vlog quality. Besides, most students have technical problems in light conditions. They are easily distracted by their surroundings, lose concentration, feeling bored, insecure when recording a vlog in front of the camera, and fear when making mistakes during speaking English. Through this vlogging, the students can improve their speaking skills in a more fun way, practice expressing themselves, increase self-confidence, and follow trends in the digital era.